Tuturan yang Berdampak Hukum Ditinjau dari Elemen dan Fungsi Konteks Sosial-Sosietal di Media Sosial Tik-Tok Indonesia - Ardhianti, Ardhianti; Indayani, Indayani (International Seminar on Austronesian Languages and Literature; Vol 9 No 1 (2021): PROCEEDINGS International Seminar on Austronesian Languages and Literature IX (ISALL IX), 2021)
This study aims to reveal speeches that are suspected of having legal implications as criminal acts of humiliation, defamation, SARA by using cyber pragmatics analysis. The cyber pragmatics analysis framework includes elements and functions of socio-social, cultural, and situational contexts and is used to examine 7 utterances originating from Tik-Tok in 2021. The research data are in the form of words, phrases, sentences, and paragraphs contained in speech in the TikTok application. . This study uses data collection procedures carried out to obtain the right data, which is able to provide answers to the problems contained in this study. To collect data, steps or steps are used, namely (1) collecting data in the form of content on the TikTok application; (2) sorting out speech that contains language that has legal implications according to the required data such as defamation, insult, and racial intolerance; (3) selecting data based on the focus of the problem that has been determined; (4) encode the content in the TikTok application, (5) describe the socio-social context of the language that has legal implications on TikTok; and (6) inferring the socio-social context of legal impacting language on TikTok. The data analysis in this study is content analysis, by analyzing the socio-social context of speech in the TikTok application that has an impact on the law. The findings of this study are the elements and functions of the socio-social context in language that have legal implications on social media related to elements of criminal acts